2020
DOI: 10.21203/rs.3.rs-26774/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitude and practice regarding COVID-19 among healthcare workers in Chitwan, Nepal

Abstract: Background COVID-19 is a viral respiratory disease that was recently recognized in humans. The number of COVID-19 cases has been gradually increasing in Nepal. The objective of this study was to evaluate knowledge, attitude and practice regarding COVID-19 among healthcare workers in Chitwan, one of the districts located in central Nepal. Methods It was a cross-sectional study conducted among healthcare workers from various health institutions located in Chitwan district of Nepal. A self-reported questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
38
4
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 13 publications
(18 reference statements)
20
38
4
1
Order By: Relevance
“…(Ryan & Deci, 2000) In this study, we found out that more than half of the respondents (53%) reported their overall level of knowledge related to COVID-19 as "competent" and 34.3% rated themselves as "pro cient". The result is consistent with other studies (Huynh, Nguyen, Vo, & Pham, 2020;Nemati et al, 2020;Nepal et al, 2020;Saqlain et al, 2020;Zhou et al, 2020) where most healthcare workers reported having good knowledge about COVID-19. This high percentage of knowledge among nurses and midwives regarding COVID-19 is due to the immense volume of information that was made public by social media.…”
Section: Discussionsupporting
confidence: 92%
“…(Ryan & Deci, 2000) In this study, we found out that more than half of the respondents (53%) reported their overall level of knowledge related to COVID-19 as "competent" and 34.3% rated themselves as "pro cient". The result is consistent with other studies (Huynh, Nguyen, Vo, & Pham, 2020;Nemati et al, 2020;Nepal et al, 2020;Saqlain et al, 2020;Zhou et al, 2020) where most healthcare workers reported having good knowledge about COVID-19. This high percentage of knowledge among nurses and midwives regarding COVID-19 is due to the immense volume of information that was made public by social media.…”
Section: Discussionsupporting
confidence: 92%
“…The current study reported that gender is considerably associated with practice score, and these findings corroborate studies done in other settings, which reported that females are more likely to take preventive and protective measures than males [26][27][28]. The study found no association between gender, age, residence, employment, and duration on ART, contrary to Nepal's studies conducted during the peak of COVID-19 [29]. This could be due to the fact that this study was conducted at a later stage of the pandemic than in Nepal when information about COVID-19 was found everywhere and accessible to all age groups.…”
Section: Discussionsupporting
confidence: 88%
“…It is time to ponder how to protect the HCPs from acquiring this disease. Studies regarding knowledge and attitude of HCPs about COVID-19 have been done in other countries [ 22 , 23 , 24 , 25 , 26 , 27 ]. However, to the best of our knowledge, none has been done with Saudi Arabian HCPs.…”
Section: Introductionmentioning
confidence: 99%